Properties of scarf joint with different angle using oil palm lumber and kelempayan / Mohd Yusmizan Ab. Manan and Ahmad Fauzi Awang @ Othman - Ab. Manan, Mohd Yusmizan; Awang @Othman, Ahmad Fauzi (2015)
The aim of this study was to determine the suitability and strength properties of scarf joint for the species oil palm (Elaeis guineensis) and kelempayan (Neolamarckia cadamba), It has been tested on different culling angles such as 30, 45, 60 and uses a type of polyvinyl acetate adhesive for both species, The samples were tested using the method of bending and compression, The results of this study show an angle of 30 species of oil palm and Kelempayan is the strongest compared to an angle of 45 and 60 for the bending test. When comparing the two species of oil palm and Kelempayan, Oil palm is stronger than Kelempayan, For the compression test, the angle 60 is more resistant than an angle of 30 and 45 for both species, Therefore, the culling angle 30 and 60 is suitable for used by industry because it is most resistant compared to the other angles. It can be concluded that species oil palm (Elaeis guineensis) and kelempayan (Neolarnarckia cadamba) can be utilized for scarf joint in the production of furniture by using the appropriate angle and furniture that want to produce.